General principles for the collection of national food consumption data in the view of a pan‐European dietary survey - European Food Safety Authority (EFSA Journal)
Abstract The availability of detailed, harmonised and high quality food consumption data at European level is a primary long term objective for EFSA which has been recognised as a top priority for collaboration with the EU Member States. This Guideline has been developed by the EFSA Expert Group on Food Consumption Data. It issues general principles to collect dietary information that can be used to estimate the nutrient intake and to assess exposure to biological agents and chemical substances considered by EFSA's Scientific Panels. It is recommended that surveys cover two non‐consecutive days and use the dietary record method for infants and children and the 24‐hour recall method for adults. It is further recommended to use a food propensity questionnaire and that supplementary information, in particular on brand name, physical characteristics of the packaging, cooking procedures and other specific information, such as fortification should be collected. Detailed information on the use of nutritional supplements by respondents should also be covered as well as physical measures of the survey participants (weight and height) along with an estimate of their physical activity level.